(Im)Possible selves in the Swiss labour market: temporalities, immigration regulations, and the production of precarious workers - Stingl, Isabella (Geoforum, 2021)
This paper uses a temporal perspective to explore the relationship between immigration regulations and the production of precarious workers. More specifically, I draw on the concept of possible selves to analyse biographical interviews with regard to the changing imaginations of possible labour market outcomes among refugees in Switzerland. Building on a growing body of literature exploring the times and temporalities of migration and border control, I shed light on how these imaginaries are co-constituted by multiple temporal regulations that are mobilised by different arms of the immigration system and often conflict with refugees’ visions of progress. In this context, I show how individuals tend to downgrade their expectations of working life and accept precarious working conditions in order to minimise these conflicts. By focusing on refugees’ experiences of waiting for, obtaining, and changing status, I further illuminate how these conflicts are not automatically resolved by moving forward within the periodised immigration system. Consequently, I argue that the identified practices of downsizing, postponing, and redirecting possible selves not only serve as strategies to resolve the gap between desired self and immediate reality but also need to be understood as expressions of extended waiting.